Dementia nursing competency in acute care settings: A concept analysis. Issue 3 (1st April 2019) - Yamaguchi, Yuko; Greiner, Chieko; Ryuno, Hirochika; Fukuda, Atsuko
Abstract: Aim: To critically analyse the concept of dementia nursing competency in acute care settings. Backgrounds: The nursing care needs of patients with dementia are increasing in acute care settings. However, a framework for the dementia nursing competency has not been explicitly outlined. Design: Rodgers' evolutionary method for concept analysis. Data Sources: Competenc* AND dementia AND nurs* AND acute OR hospital OR clinical were selected from the MEDLINE, CINAHL, PsycINFO, CiNii, and Google Scholar for publication from 2006 to 2017. Review Methods: All 29 articles were identified. Data were analysed with a particular focus on the attributes, antecedents, and consequences of the concept. Results: Six attributes were identified: respecting patient individuality, applying ethical considerations, providing person‐centred care, possessing responsibility, coordinating external environments, and possessing care coordination and facilitation skills. Identified antecedents included building theoretical and clinical knowledge, developing an awareness of dementia and its risk behaviours, performing assessments of dementia nursing practice, developing relationships with patients with dementia, and applying a team approach. Applying the competency led to positive consequences for patients, nurses, and patient‐nurse and nursing team relationships. Conclusion: Developing the dementia nursing competency results in stronger emotional interventions and adds a human‐to‐human connection. SUMMARY STATEMENT: What is already known about this topic? The roles of dementia nurses are becoming more important in acute care settings in countries with ageing populations because patient age is increasing as a result of advancements in medical technology, and the age ranges of patients undergoing operations are expanding. However, nurses in acute care settings generally devote little time to communicating with patients with dementia or gaining an understanding of their feelings. As a result, they lack knowledge and awareness of dementia nursing care. In previous research in the nursing field, the concept of competency has been based on Benner's nursing theory, which identified five levels of nursing in terms of developing skills and understanding patient care: novice, advanced beginner, competent, proficient, and expert. Dementia nursing competency has been defined as person‐centred care, applying evidenced‐based approaches, recognizing dementia, improving communication and assessment skills, developing knowledge as a nursing specialist, and environmental management of patients and families in elderly care facilities. What this paper adds? This concept analysis provides a conceptual basis for the development of dementia nursing competency in acute care settings, which consists of attributes, antecedents, and consequences. Our results show that nurses with dementia nursing competency gain a deeper understanding of patients with dementia, which could lead to positive outcomes for such patients. Possessing dementia nursing competency results in stronger emotional interventions and adds a human‐to‐human connection. The implications of this paper: This concept analysis clarifies the present concept of dementia nursing competency in acute care settings and provides a foundation for nurses to respect each patient with dementia as an individual, and to respect patients' autonomy and dignity in balance with managing risk. These findings may lead to improved comfort and well‐being for patients with dementia during hospital admissions and may enhance safety, decrease admission duration and readmissions frequency, ensure positive reactions concerning communication behaviour, and decrease the use of needless medication.